Diseminasi Maggot sebagai Pakan Lokal Alternatif Sumber Protein Ayam Kampung pada Kegiatan PKM Kelompok Tani-Ternak Liku Labbua di Kecamatan Bangkala Barat Kabupaten Jeneponto - Sri Purwanti; Muhammad Rachman Hakim; Ilham Syarif (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
A technology dissemination program aimed at the community is carried out with a focus on the main problems experienced by partners and provides sustainable solutions based on the potential and resources owned by internal partners themselves. The implementation of this program aims to increase the capacity of farmers by providing information on the potential utilization of natural resources in their land. That resources especially agricultural and livestock waste that can be used as a medium for developing feed ingredients from insects i.e., BSF larvae (maggot). It will be used as an alternative feed for native chickens. Service activities are carried out through several stages including preparation, socialization, extension and demonstrations, as well as assistance so that farmers can independently carry out technology transfer packages themselves. During the activity, group members showed a high level of participation. Demonstration plots for rearing BSF larvae followed by feeding either processed or fresh larvae to native chickens. It was focused on one member of the group who was more ready to receive the technology package. From the evaluation results obtained that partners have additional information on how to cultivate maggot as an alternative source of protein feed, get to know local feed raw materials around and management of free-range chickens. Maggot cultivation results that are harvested at the age of 15 days are directly given to members’ chickens. At the end of the service activities, partners get a lot of experience and new skills, namely maggot cultivation.